Effects of dynamic lycra orthosis as an adjunct to rehabilitation after botulinum toxin-A injection of the upper-limb in adults following stroke: A single-blinded randomized controlled pilot study - KARADAĞ SAYGI, NAİME EVRİM; GÜNDÜZ, OSMAN HAKAN (TAYLOR & FRANCIS LTD, 2020)
Background: Dynamic lycra splints are proposed to modify hypertonicity due to their characteristics - neutral warmth, circumferential pressure, and creating a low-intensity prolonged stretch on hypertonic muscles - to contribute to increased sensory awareness of the involved limb. Objectives: The aim of this study was to investigate the effects of dynamic lycra orthosis as an adjunct to botulinum toxin-A injection and rehabilitation of the upper-limb in adults following stroke. Methods: Patients who had suffered a stroke more than three months previously were randomized into two groups: lycra sleeve plus rehabilitation (n = 10) and only-rehabilitation group (n = 10). After botulinum toxin injection, both groups underwent an upper-limb rehabilitation program. The intervention group wore a lycra sleeve for eight hours a day, five days a week for three weeks in addition to the rehabilitation program. Fugl Meyer upper-limb motor score, Motricity index, Modified Ashworth scale, Box and Block test, Stroke Impact Scale and change in touch-detection thresholds of the fingers measured via Semmes-Weinstein monofilaments were assessed by blinded investigators at before treatment, post-treatment (at 3 weeks) and three months post-treatment. This trial is registered with Clinicaltrials.gov, number NCT03546959. Results: There were no differences between groups in terms of Fugl Meyer upper-limb motor score, Motricity Index, Modified Ashworth scale, Box and Block test, Stroke Impact Scale and change in light touch threshold at any follow-up time points. Conclusions: Using lycra splints as an adjunct to an upper-limb rehabilitation program after stroke did not provide additional benefit in spasticity, upper-limb motor function, light touch threshold of fingers or stroke-specific quality-of-life.
Keywords: Botulinum toxin; lycra; orthoses; upper limb; rehabilitation; stroke; SPASTICITY